"Just one bad high:" Considering synthetic cannabinoid outcome expectancies in adolescents. Issue 8 (17th October 2016) - Mathai, David S.; Verrico, Christopher D.; Shorter, Daryl; Coverdale, John H.; Kosten, Thomas R.
Abstract : Background/Objectives: Certain medical consequences seem unique to synthetic cannabinoid (SC) and not cannabis use. We report the case of an adolescent, whose drug expectancies appear to minimize the severity of SC‐related adverse events. Methods/Results: An 18‐year‐old male presented with altered mental status and seizure, complicated by respiratory failure. He was stabilized and on discharge, despite counseling on the harms of SC usage, the patient planned to resume use, insisting that the hospitalization was "just one bad high". Discussion/Conclusions/Scientific Significance: Diminished negative expectancies related to SC use among adolescents may reflect generalizations from cannabis. Effective interventions should counter cannabis‐related expectancies of minimal harm. (Am J Addict 2016;25:620–622)